Exploring an online clinical competency assessment: an alternative to a traditional in-person assessment for internationally trained physiotherapists - Brooke Flew; Lucy Chipchase; Darren Lee; Jodie A. McClelland (BMC Medical Education)
Abstract Background The assessment of clinical competence is crucial for the education and accreditation of health professionals. Although traditional in-person methods, such as objective structured clinical examinations and case-based clinical assessments are widely used, the COVID-19 pandemic prompted the exploration of online formats. This study examined conducting a clinical case-based assessment in an online environment as an alternative to a traditional in-person assessment for evaluating the competence of internationally trained physiotherapists seeking registration in Australia. Methods A single-cohort observational study was conducted, where participants completed both online and in-person assessments. Participants were internationally trained physiotherapists seeking registration in Australia. Participants were scored as pass/fail on 8 domains and for overall outcome. Data were analysed by calculating pass/fail rates, absolute agreement, false negative and positive rates and predictive values. Results There was a 63% agreement in outcomes between each format, with comparable pass rates (online: 54%, in-person: 68%, p = 0.09). The online assessment demonstrated a strong positive predictive value (79%), indicating its potential to regularly predict competence as determined by the in-person assessment. However, online pass rates were significantly lower than in-person pass rates (60% and 78% respectively, p = 0.04) for the domain that scored competency in hands-on skills. Conclusion The findings suggest that online assessment could serve as a viable alternative to the in-person assessment. However, further refinements may be needed to address hands-on skill assessment in online assessments. This study adds to the current evidence base supporting the use of online assessments as an alternative to traditional in-person methods for evaluating clinical competence.